A classification of abdominal lymphatic perfusion patterns after Fontan surgery - Schroeder, Christian; Moosmann, Julia; Cesnjevar, Robert; Purbojo, Ariawan; Rompel, Oliver; Dittrich, Sven (European Journal of Cardio-Thoracic Surgery, 2022)
OBJECTIVES: Complications after Fontan surgery have been associated with arise and classification of abnormal thoracic lymphatic perfusion pattern. This study compiles abnormal abdominal lymphatic perfusion patterns and investigates their impact on serum protein readings.
CRIS-Team WoS Importer:2022-03-11